A GH4099 high-temperature alloy complex structure corrosion-resistant pipe fitting and a preparation method thereof

CN122625374BActive Publication Date: 2026-10-20上海一郎合金材料有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611132740.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-20
Estimated Expiration
2046-07-28

AI Technical Summary

Technical Problem

[0004]然而,现有的管件成形工艺存在固有局限,传统的热挤压、锻造工艺仅适用于简单圆形截面的直管类管件,对于带有异形内腔、空间弯曲、变壁厚、多流道集成特征的复杂结构管件,通常需要采用分段成形后焊接拼接、大量机械加工去除余量的方式制备,不仅材料利用率低、加工周期长,且热锻毛坯普遍存在变形量大、难切削的特点,管件的尺寸精度与表面质量难以稳定控制

Benefits of technology

1、本发明在管件表面构建的原位梯度改性层,表层由硼硅酸钙复盐相与铬、铝元素富集的致密氧化物相共同构成,可在高温氧化及含硫、含氯复合腐蚀环境中形成连续稳定的物理阻隔屏障,有效阻滞腐蚀介质向基体内部渗透,缓解酸性熔盐对基体表面的溶解破坏作用,显著提升管件的耐高温热腐蚀与高温氧化性能。改性层通过扩散过渡层与基体实现冶金结合,硼、硅、钙元素沿深度方向呈连续梯度递减分布,可有效降低改性层与基体间的物性差异与界面应力,避免高温冷热循环工况下改性层发生开裂、剥落,保障长期服役过程中防护性能的稳定性;对于焊接成形的复杂管件,改性层可完整覆盖焊缝及热影响区,弥补该区域耐蚀性能偏低的短板,消除焊接结构的腐蚀薄弱环节,尤其适用于管件变径、弯折等流体湍流区域,可有效抵御冲蚀与腐蚀的耦合损伤。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application relates to the technical field of alloy material, and more particularly to a GH4099 high-temperature alloy complex structure corrosion-resistant pipe fitting and a preparation method thereof, which comprises the following steps: firstly, a GH4099 high-temperature alloy pipe fitting blank is polished and degreased and cleaned, and then vacuum solid solution is performed to obtain a pipe fitting matrix; secondly, modified suspension slurry is prepared by taking calcium hydroxide, boric acid and fumed silica as solid components; thirdly, the slurry is coated on the inner and outer walls of the pipe fitting by using rotary coating and air spraying respectively, and then dried to form a base film layer; and finally, the finished product is obtained by performing argon protection segmented heating treatment and two-stage aging treatment. The present application can construct an in-situ gradient modified layer on the surface of the pipe fitting, block the penetration of corrosive medium by means of the synergistic effect of the surface layer complex salt and oxide, relieve the interface thermal stress by using the gradient transition metallurgical bonding structure, and simultaneously improve the high-temperature composite hot corrosion resistance and the cold and hot cycle spalling resistance of the pipe fitting.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of alloy materials technology, and in particular to a GH4099 high-temperature alloy complex structure corrosion-resistant pipe fitting and its preparation method. Background Technology

[0002] In the gas guiding and cooling pipelines of aero-engine combustion chambers and afterburners, as well as the high-temperature process pipelines of gas turbine waste heat recovery and petrochemical hydrogenation units, the pipe fittings not only need to maintain structural strength and creep resistance for long periods under high-temperature environments, but also need to withstand multiple corrosive effects from high-temperature flue gas, sulfur-containing media, and chloride ion atmospheres. Meanwhile, some pipelines are designed with complex structures featuring irregular cross-sections, varying diameters and wall thicknesses, and multi-channel integration to achieve fluid control, space adaptation, and weight reduction requirements, placing extremely high demands on material properties and manufacturing processes. Traditional austenitic stainless steel and low-to-medium grade heat-resistant alloys can no longer simultaneously meet the dual requirements of high-temperature strength and corrosion resistance. Nickel-based high-temperature alloys, with their excellent high-temperature mechanical properties and chemical stability, are gradually becoming the core material choice for pipe fittings operating under extreme conditions.

[0003] GH4099, a typical Ni-Cr-based precipitation-hardening wrought superalloy, can withstand long-term service at around 900℃ and short-term higher temperatures. It possesses excellent high-temperature strength, weldability, and resistance to oxidation and corrosion. Currently, it is widely used in hot-end thin-plate welded structures such as aero-engine combustion chamber shells and heat shields, and is gradually expanding into high-temperature corrosion pipeline scenarios in the energy and chemical industries. The alloy's corrosion resistance primarily relies on a dense oxide protective film formed on its surface. A stable protective layer is generated through the selective oxidation of chromium and aluminum, combined with the microalloying effect of elements such as molybdenum and niobium, exhibiting good corrosion resistance in high-temperature oxidizing and sulfur-containing atmospheres.

[0004] However, existing pipe forming processes have inherent limitations. Traditional hot extrusion and forging processes are only suitable for straight pipes with simple circular cross-sections. For complex pipes with irregular internal cavities, spatial bends, variable wall thicknesses, and multi-channel integration, segmented forming followed by welding and extensive machining to remove excess material is usually required. This not only results in low material utilization and long processing cycles, but also in the large deformation and difficulty in machining of hot-forged blanks, making it difficult to consistently control the dimensional accuracy and surface quality of the pipes. Furthermore, welded pipes exhibit uneven microstructure and residual stress concentration in the weld seam and heat-affected zone. Under corrosive media, the weld area is highly susceptible to corrosion, inducing intergranular corrosion, stress corrosion cracking, and other failure modes, significantly reducing the overall service life and operational reliability of the pipes. In recent years, additive manufacturing technology has provided a new path for the forming of complex structural pipes, enabling the integrated near-net-shape forming of irregular structures. However, GH4099 alloys prepared by processes such as selective laser melting have metallurgical defects such as cellular subgrain structure and micropores. Without a suitable heat treatment regime, its corrosion resistance, such as hot corrosion resistance, is significantly lower than that of forged materials. Furthermore, problems such as the uniformity of forming density and residual stress control of large-size pipes have not yet been effectively solved.

[0005] Furthermore, the corrosion resistance of pipe fittings is insufficiently adapted to complex operating conditions. GH4099 alloy can form a stable protective oxide film in a single high-temperature oxidizing environment, exhibiting good corrosion resistance. However, in complex media conditions such as combined hot corrosion environments containing sulfates and chlorides, and marine atmospheres and sulfur-containing flue gas, the surface oxide film is easily destroyed by corrosive media, leading to acidic dissolution-type hot corrosion, and the corrosion process is significantly accelerated. For pipe fittings with corrosive media flowing inside, the inner wall is in direct contact with the fluid medium. In turbulent fluid areas such as flow channel corners and diameter changes, the coupling effect of erosion and corrosion further exacerbates material loss. Existing processes cannot achieve uniform and effective surface protection modification for the irregularly shaped inner cavities of complex pipe fittings, and relying solely on the intrinsic corrosion resistance of the material is insufficient to meet the requirements for long-term service. Summary of the Invention

[0006] To address the problems mentioned in the background section, this invention provides a GH4099 high-temperature alloy complex structure corrosion-resistant pipe fitting and its preparation method.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: This invention provides, on one hand, a method for preparing GH4099 high-temperature alloy corrosion-resistant pipe fittings, and on the other hand, a GH4099 high-temperature alloy corrosion-resistant pipe fitting itself. The specific technical solutions are as follows: A method for preparing GH4099 high-temperature alloy corrosion-resistant pipe fittings, the method comprising the following steps: S1. After the GH4099 high-temperature alloy pipe blank is successively ground, degreased and cleaned, it is subjected to vacuum solution treatment to obtain the pipe substrate.

[0008] In some embodiments of the present invention, in step S1, the surface polishing is carried out sequentially using 400#, 800#, and 1200# wet sandpaper until the surface roughness Ra≤0.8μm; the degreasing cleaning is acetone ultrasonic cleaning followed by rinsing with anhydrous ethanol and drying with nitrogen.

[0009] In some embodiments of the present invention, in step S1, before vacuum solution treatment, a high-temperature resistant ceramic fixture is used for furnace loading and positioning; the vacuum solution treatment process is as follows: the vacuum degree in the furnace is ≤5×10⁻³Pa, the temperature is raised to 600-700℃ and held for 20-30 minutes to homogenize the furnace charge, the temperature is raised to 1100-1140℃ at a rate of 8-12℃ / min, held for 1.5-2.5 hours, and after the holding period, argon gas is introduced for quenching, with a cooling rate ≥50℃ / min.

[0010] S2. A modified suspension slurry was prepared by pre-dispersing and planetary ball milling using calcium hydroxide, boric acid, and fumed silica as solid phase components, deionized water as dispersion medium, and sodium carboxymethyl cellulose as a dispersing medium.

[0011] In some embodiments of the present invention, in step S2, the mass ratio of calcium hydroxide:boric acid:fumed silica:deionized water:sodium carboxymethyl cellulose is (16-20):(26-30):(10-14):(40-44):(0.6-1.0).

[0012] In some embodiments of the present invention, in step S2, the calcium hydroxide, boric acid, and fumed silica are all of analytical grade, and the original particle size of the fumed silica is 10-20 nm, and the specific surface area is 150-250 m² / g.

[0013] In some embodiments of the present invention, in step S2, the pre-dispersion is carried out by mechanical stirring at room temperature, with a stirring rate of 200-300 r / min and a stirring time of 30-60 min.

[0014] In some embodiments of the present invention, in step S2, the planetary ball mill uses zirconia grinding balls with a ball-to-material mass ratio of (4-6):1, a ball milling speed of 280-320 r / min, a ball milling time of 1.5-2.5 h, and the solid content of the resulting slurry is 50-60 wt%. The ball milling process adopts an intermittent operation mode, with a 5-minute stop after every 30 minutes of continuous ball milling to control the slurry temperature. After the ball milling is completed, the slurry is filtered through a 200-300 mesh standard sieve to remove slag.

[0015] S3. The modified suspension slurry is coated on the inner wall of the pipe fitting using a rotary coating method, and the modified suspension slurry is coated on the outer wall of the pipe fitting using an air spraying method. After drying, a film layer is formed on the inner and outer surfaces of the pipe fitting.

[0016] In some embodiments of the present invention, in step S3, the substrate of the pipe is preheated to 40-60°C before coating; after the inner wall coating is completed, it is left to stand for 5-10 minutes until the inner wall slurry flows naturally before the outer wall coating is carried out.

[0017] In some embodiments of the present invention, in step S3, the process parameters of the rotary coating are as follows: after the two ends of the pipe are sealed, it is rotated horizontally at a speed of 50-70 r / min and a rotation time of 10-20 min; during the rotation, the pipe synchronously swings back and forth along the axial direction at 10°-15°.

[0018] In some embodiments of the present invention, in step S3, the process parameters of the air spraying are as follows: the spraying air pressure is 0.15-0.25MPa, the spraying distance is 10-20cm, the gun speed is 8-12cm / s, 1-3 coats are sprayed, and the interval between coats is 3-8min; the ambient temperature of the spraying operation is controlled at 20-30℃, and the relative humidity is controlled at 40%-60%.

[0019] In some embodiments of the present invention, in step S3, the drying temperature is 110-130℃, the drying time is 1.5-2.5h, and the thickness deviation between the inner and outer walls of the obtained raw film layer is ≤±2μm; during the drying process, the tube is kept at a low speed of 10-20r / min for horizontal rotation, and the overall thickness of the raw film layer is controlled at 25-38μm.

[0020] S4. Under an argon protective atmosphere, the pipe fittings coated with the base film are subjected to segmented heating heat treatment and then cooled to room temperature.

[0021] In some embodiments of the present invention, in step S4, the pipes coated with the base film are vertically suspended in the furnace before heat treatment to avoid the base film from contacting and scratching the furnace.

[0022] In some embodiments of the present invention, in step S4, the segmented heating heat treatment process is as follows: heating to 380-420℃ at a rate of 4-6℃ / min and holding for 0.5-1.5h; then heating to 880-920℃ at a rate of 2-4℃ / min and holding for 3-5h; high-purity argon gas is introduced throughout the heat treatment process, and the oxygen volume fraction in the furnace is ≤10×10⁻ 6 During the heat preservation stage, the argon gas in the furnace is maintained at a slight positive pressure of 0.02-0.05 MPa. After the heat preservation is completed, argon gas is used for convection cooling with a cooling rate of ≥10℃ / min and the gas flow rate of argon gas for convection cooling is controlled at 15-25 m³ / h.

[0023] S5. Perform a two-stage aging treatment on the pipe fittings under an argon protective atmosphere, and then cool them to room temperature in the furnace.

[0024] In some embodiments of the present invention, in step S5, the secondary aging process is as follows: the temperature is increased to 730-770°C at a rate of 4-6°C / min, and held for 10-14 hours. After the holding period, the temperature is cooled with the furnace. When the temperature is reduced to 630-670°C with the furnace, the second-stage aging process is carried out for 6-10 hours. After the holding period, the temperature is cooled with the furnace to room temperature.

[0025] A GH4099 high-temperature alloy corrosion-resistant pipe fitting includes a GH4099 nickel-based high-temperature alloy pipe fitting substrate. The inner and outer surfaces of the pipe fitting substrate are provided with an in-situ gradient modification layer. The in-situ gradient modification layer includes a surface modification layer and a diffusion transition layer from the surface to the inside. The diffusion transition layer is metallurgically bonded to the pipe fitting substrate.

[0026] In some embodiments of the present invention, the thickness of the surface modification layer is 20-30 μm, and the thickness of the diffusion transition layer is 5-8 μm.

[0027] In some embodiments of the present invention, the surface modification layer mainly comprises a calcium borosilicate complex salt phase and a dense oxide phase enriched with chromium and aluminum elements, and the boron, silicon and calcium elements in the diffusion transition layer are distributed in a continuous gradient decreasing along the depth direction.

[0028] In some embodiments of the present invention, the overall thickness uniformity deviation of the in-situ gradient modified layer is ≤ ±3 μm, and the thickness deviation of the modified layer in complex structural areas such as pipe diameter changes and bends is ≤ ±5 μm.

[0029] The beneficial effects of this invention are: 1. The in-situ gradient modification layer constructed on the surface of the pipe fitting in this invention consists of a calcium borosilicate complex salt phase and a dense oxide phase enriched with chromium and aluminum. This layer forms a continuous and stable physical barrier in high-temperature oxidation and sulfur- and chlorine-containing composite corrosion environments, effectively preventing the penetration of corrosive media into the substrate and mitigating the dissolving and damaging effects of acidic molten salts on the substrate surface. This significantly improves the pipe fitting's resistance to high-temperature corrosion and oxidation. The modified layer achieves metallurgical bonding with the substrate through a diffusion transition layer. The boron, silicon, and calcium elements are distributed in a continuous gradient decreasing along the depth direction, effectively reducing the difference in physical properties and interfacial stress between the modified layer and the substrate. This prevents cracking and peeling of the modified layer under high-temperature thermal cycling conditions, ensuring the stability of protective performance during long-term service. For complex welded pipe fittings, the modified layer can completely cover the weld and heat-affected zone, compensating for the low corrosion resistance in this area and eliminating weak points in the welded structure. It is particularly suitable for fluid turbulence areas such as pipe diameter changes and bends, effectively resisting the coupled damage of erosion and corrosion.

[0030] 2. This invention employs a process combining vacuum solution treatment and two-stage aging treatment, which allows for the uniform precipitation of reinforcing phases in the pipe fitting matrix. Simultaneously, it eliminates residual stress generated during forming, improves grain boundary conditions, enhances the high-temperature mechanical properties and grain boundary corrosion resistance of the matrix, avoids localized corrosion failure caused by differences in microstructure in different parts, effectively inhibits the initiation of intergranular corrosion and stress corrosion cracking, and achieves a synergistic improvement in the matrix's mechanical properties and corrosion resistance. Addressing the significant differences in deformation degrees in different parts of complex pipe fittings, the segmented heating and graded heat treatment process ensures uniform temperature field across all parts of the fitting, reduces performance fluctuations caused by structural differences, and improves the overall consistency of the fitting's performance.

[0031] 3. This invention employs a differentiated coating scheme, using a rotary coating method to prepare the inner wall modified layer and an air spraying method to prepare the outer wall modified layer. Combined with process control measures such as pipe preheating, slurry leveling, and axial oscillation, it effectively ensures the uniformity of the inner and outer wall film thickness of complex pipe structures. In particular, it achieves complete coverage of difficult-to-coat areas such as irregularly shaped cavities and variable-diameter channels, keeping the thickness deviation between the inner and outer walls at a low level. This avoids localized weak points in protection caused by uneven film thickness, ensuring the uniformity of the protective performance across the entire surface of the pipe. Simultaneously, the segmented heating heat treatment regime allows the slurry components to react gradually and diffuse in an orderly manner, avoiding defects such as film cracking and pinholes caused by rapid heating, thus improving the density and integrity of the modified layer. Detailed Implementation

[0032] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0033] Example 1 This embodiment provides a method for preparing GH4099 high-temperature alloy corrosion-resistant pipe fittings, the specific steps of which are as follows: S1. The GH4099 high-temperature alloy pipe blank was successively polished with 400#, 800#, and 1200# wet sandpaper until the surface roughness was 0.8μm. After ultrasonic cleaning with acetone, rinsing with anhydrous ethanol, and drying with nitrogen, it was placed in the furnace using high-temperature resistant ceramic fixtures for vacuum solution treatment; the vacuum degree inside the furnace was 5×10. -3 Pa, heat to 600℃ and hold for 20 min to homogenize the temperature, then heat to 1100℃ at a rate of 8℃ / min and hold for 1.5 h. After holding, argon gas is introduced for quenching at a cooling rate of 50℃ / min to obtain the pipe base.

[0034] S2. By mass ratio, 16 parts calcium hydroxide, 26 parts boric acid, and 10 parts fumed silica were used as solid components. 40 parts deionized water and 0.6 parts sodium carboxymethyl cellulose were added. After pre-dispersion by mechanical stirring at 200 r / min for 30 min at room temperature, a modified suspension slurry was prepared by planetary ball milling. Zirconia grinding balls were used for ball milling, with a ball-to-material mass ratio of 4:1, a ball milling speed of 280 r / min, and a ball milling time of 1.5 h. The resulting slurry had a solid content of 50 wt%.

[0035] S3. Preheat the pipe substrate to 40℃, and apply modified suspension slurry to the inner wall of the pipe using a rotary coating method. After sealing both ends of the pipe, rotate it horizontally at a speed of 50 r / min for 10 min. After standing for 5 min to allow the slurry on the inner wall to level, apply slurry to the outer wall of the pipe using an air spraying method. The spraying air pressure is 0.15 MPa, the spraying distance is 10 cm, the gun speed is 8 cm / s, and one coat is applied. After coating, dry at 110℃ for 1.5 h. During the drying process, keep the pipe rotating at a low speed of 10 r / min to obtain a plain film layer on both the inner and outer walls with an overall thickness of about 25 μm.

[0036] S4. The pipe fittings coated with the base film are vertically suspended in the furnace and subjected to segmented heat treatment under an argon protective atmosphere: the temperature is increased to 380℃ at a rate of 4℃ / min and held for 0.5h; then the temperature is increased to 880℃ at a rate of 2℃ / min and held for 3h; high-purity argon is introduced throughout the process, and the oxygen volume fraction in the furnace is 10×10⁻⁶. -6 During the heat preservation stage, a slight positive pressure of 0.02 MPa was maintained; after the heat preservation was completed, argon convection cooling was used with a gas flow rate of 15 m³ / s. 3 / h, cooling rate 10℃ / min, cooling to room temperature.

[0037] S5. Under an argon protective atmosphere, the pipe fittings undergo a two-stage aging treatment: the temperature is increased to 730℃ at a rate of 4℃ / min and held for 10 hours; the temperature is then reduced to 630℃ in the furnace and held for 6 hours; after the holding period, the pipe fittings are further cooled to room temperature in the furnace to obtain the finished pipe fittings.

[0038] Example 2 This embodiment provides a method for preparing GH4099 high-temperature alloy corrosion-resistant pipe fittings, the specific steps of which are as follows: S1. The GH4099 high-temperature alloy pipe blank was successively polished with 400#, 800#, and 1200# wet sandpaper until the surface roughness was 0.8μm. After ultrasonic cleaning with acetone, rinsing with anhydrous ethanol, and drying with nitrogen, it was placed in the furnace using high-temperature resistant ceramic fixtures for vacuum solution treatment; the vacuum degree inside the furnace was 5×10. -3Pa, heat to 650℃ and hold for 25 min to homogenize the temperature, then heat to 1120℃ at a rate of 10℃ / min and hold for 2.0 h. After holding, argon gas is introduced for quenching at a cooling rate of 50℃ / min to obtain the pipe base.

[0039] S2. By mass ratio, 18 parts calcium hydroxide, 28 parts boric acid, and 12 parts fumed silica were used as solid components. 42 parts deionized water and 0.8 parts sodium carboxymethyl cellulose were added. After pre-dispersion by mechanical stirring at 250 r / min for 45 min at room temperature, a modified suspension slurry was prepared by planetary ball milling. Zirconia grinding balls were used for ball milling, with a ball-to-material mass ratio of 5:1, a ball milling speed of 300 r / min, and a ball milling time of 2.0 h. The resulting slurry had a solid content of 55 wt%.

[0040] S3. Preheat the pipe substrate to 50℃, and apply modified suspension slurry to the inner wall of the pipe using a rotary coating method. After sealing both ends of the pipe, rotate it horizontally at a speed of 60 r / min for 15 min. During the rotation, the pipe simultaneously swings back and forth 12° along the axial direction. After standing for 7 min to allow the slurry on the inner wall to level, apply slurry to the outer wall of the pipe using an air spraying method. The spraying air pressure is 0.20 MPa, the spraying distance is 15 cm, the gun speed is 10 cm / s, and two coats are applied with a 5 min interval between coats. After coating, dry at 120℃ for 2.0 h. During the drying process, keep the pipe rotating at a low speed of 15 r / min to obtain a plain film layer on both the inner and outer walls with an overall thickness of approximately 32 μm.

[0041] S4. The pipe fittings coated with the base film are vertically suspended in the furnace and subjected to segmented heat treatment under an argon protective atmosphere: the temperature is increased to 400℃ at a rate of 5℃ / min and held for 1.0 h; then the temperature is increased to 900℃ at a rate of 3℃ / min and held for 4 h; high-purity argon is introduced throughout the process, and the oxygen volume fraction in the furnace is 10×10⁻⁶. -6 During the heat preservation stage, a slight positive pressure of 0.035 MPa was maintained; after the heat preservation was completed, argon convection cooling was used with a gas flow rate of 20 m³ / h. 3 / h, cooling rate 10℃ / min, cooling to room temperature.

[0042] S5. Under an argon protective atmosphere, the pipe fittings undergo a two-stage aging treatment: the temperature is increased to 750℃ at a rate of 5℃ / min and held for 12 hours; the temperature is then reduced to 650℃ in the furnace and held for 8 hours; after the holding period, the temperature is further reduced in the furnace to room temperature to obtain the finished pipe fittings.

[0043] Example 3 This embodiment provides a method for preparing GH4099 high-temperature alloy corrosion-resistant pipe fittings, the specific steps of which are as follows: S1. The GH4099 high-temperature alloy pipe blank was successively polished with 400#, 800#, and 1200# wet sandpaper until the surface roughness was 0.8μm. After ultrasonic cleaning with acetone, rinsing with anhydrous ethanol, and drying with nitrogen, it was placed in the furnace using high-temperature resistant ceramic fixtures for vacuum solution treatment; the vacuum degree inside the furnace was 5×10. -3 Pa, heat to 700℃ and hold for 30 min to homogenize the temperature, then heat to 1140℃ at a rate of 12℃ / min and hold for 2.5 h. After holding, argon gas is introduced for quenching at a cooling rate of 50℃ / min to obtain the pipe base.

[0044] S2. By mass ratio, 20 parts calcium hydroxide, 30 parts boric acid, and 14 parts fumed silica were used as solid components. 44 parts deionized water and 1.0 part sodium carboxymethyl cellulose were added. After pre-dispersion by mechanical stirring at 300 r / min for 60 min at room temperature, a modified suspension slurry was prepared by planetary ball milling. Zirconia grinding balls were used for ball milling, with a ball-to-material mass ratio of 6:1, a ball milling speed of 320 r / min, and a ball milling time of 2.5 h. The resulting slurry had a solid content of 60 wt%.

[0045] S3. Preheat the pipe substrate to 60℃, and apply modified suspension slurry to the inner wall of the pipe using a rotary coating method. After sealing both ends of the pipe, rotate it horizontally at a speed of 70 r / min for 20 min. During the rotation, the pipe will simultaneously swing back and forth 15° along the axial direction. After standing for 10 min to allow the slurry on the inner wall to level, apply slurry to the outer wall of the pipe using an air spraying method. The spraying air pressure is 0.25 MPa, the spraying distance is 20 cm, the gun speed is 12 cm / s, and three coats are applied with an 8 min interval between coats. After coating, dry at 130℃ for 2.5 h. During the drying process, keep the pipe rotating at a low speed of 20 r / min to obtain a plain film layer on both the inner and outer walls with an overall thickness of approximately 38 μm.

[0046] S4. The pipe fittings coated with the base film are vertically suspended in the furnace and subjected to segmented heat treatment under an argon protective atmosphere: the temperature is increased to 420℃ at a rate of 6℃ / min and held for 1.5h; then increased to 920℃ at a rate of 4℃ / min and held for 5h; high-purity argon is introduced throughout the process, and the oxygen volume fraction in the furnace is 10×10⁻⁶. -6 During the heat preservation stage, a slight positive pressure of 0.05 MPa was maintained; after the heat preservation was completed, argon convection cooling was used with a gas flow rate of 25 m³ / h. 3 / h, cooling rate 10℃ / min, cooling to room temperature.

[0047] S5. Under an argon protective atmosphere, the pipe fittings undergo a two-stage aging treatment: the temperature is increased to 770℃ at a rate of 6℃ / min and held for 14 hours; the temperature is then reduced to 670℃ in the furnace and held for 10 hours; after the holding period, the pipe fittings are cooled to room temperature in the furnace to obtain the finished pipe fittings.

[0048] Example 4 This embodiment provides a method for preparing GH4099 high-temperature alloy corrosion-resistant pipe fittings, the specific steps of which are as follows: S1. The GH4099 high-temperature alloy pipe blank was successively polished with 400#, 800#, and 1200# wet sandpaper until the surface roughness was 0.8μm. After ultrasonic cleaning with acetone, rinsing with anhydrous ethanol, and drying with nitrogen, it was placed in the furnace using high-temperature resistant ceramic fixtures for vacuum solution treatment; the vacuum degree inside the furnace was 5×10. -3 Pa, heat to 620℃ and hold for 22 min to homogenize the temperature, then heat to 1110℃ at a rate of 9℃ / min and hold for 2.0 h. After holding, argon gas is introduced for quenching at a cooling rate of 50℃ / min to obtain the pipe base.

[0049] S2. By mass ratio, 17 parts calcium hydroxide, 27 parts boric acid, and 11 parts fumed silica were used as solid phase components. 41 parts deionized water and 0.7 parts sodium carboxymethyl cellulose were added. After pre-dispersion by mechanical stirring at 220 r / min for 35 min at room temperature, a modified suspension slurry was prepared by planetary ball milling. Zirconia grinding balls were used for ball milling, with a ball-to-material mass ratio of 4.5:1. The ball milling speed was 290 r / min, and the milling time was 2.0 h. The milling process was stopped for 5 min every 30 min for temperature control. The slurry after ball milling was filtered through a 250 mesh standard sieve, and the solid content of the obtained slurry was 52 wt%.

[0050] S3. Preheat the pipe substrate to 45℃, and apply modified suspension slurry to the inner wall of the pipe using a rotary coating method. After sealing both ends of the pipe, rotate it horizontally at a speed of 55 r / min for 12 min. During the rotation, the pipe simultaneously swings back and forth 11° along the axial direction. After standing for 6 min to allow the slurry on the inner wall to level, apply slurry to the outer wall of the pipe using an air spraying method. The spraying air pressure is 0.18 MPa, the spraying distance is 12 cm, the gun speed is 9 cm / s, and two coats are applied with a 4 min interval between coats. After coating, dry at 115℃ for 2.0 h. During the drying process, keep the pipe rotating at a low speed of 12 r / min to obtain a plain film layer on both the inner and outer walls with an overall thickness of approximately 28 μm.

[0051] S4. The pipe fittings coated with the base film are vertically suspended in the furnace and subjected to segmented heat treatment under an argon protective atmosphere: the temperature is increased to 390℃ at a rate of 5℃ / min and held for 0.8h; then increased to 890℃ at a rate of 3℃ / min and held for 3.5h; high-purity argon is introduced throughout the process, and the oxygen volume fraction in the furnace is 10×10⁻⁶. -6 During the heat preservation stage, a slight positive pressure of 0.03 MPa was maintained; after the heat preservation was completed, argon convection cooling was used with a gas flow rate of 18 m³ / s. 3 / h, cooling rate ≥10℃ / min, cooling to room temperature.

[0052] S5. Under an argon protective atmosphere, the pipe fittings undergo a two-stage aging treatment: the temperature is increased to 740℃ at a rate of 5℃ / min and held for 11 hours; the temperature is then reduced to 640℃ in the furnace and held for 7 hours; after the holding period, the temperature is further reduced in the furnace to room temperature to obtain the finished pipe fittings.

[0053] Example 5 This embodiment provides a method for preparing GH4099 high-temperature alloy corrosion-resistant pipe fittings, the specific steps of which are as follows: S1. The GH4099 high-temperature alloy pipe blank was successively polished with 400#, 800#, and 1200# wet sandpaper until the surface roughness was 0.8μm. After ultrasonic cleaning with acetone, rinsing with anhydrous ethanol, and drying with nitrogen, it was placed in the furnace using high-temperature resistant ceramic fixtures for vacuum solution treatment; the vacuum degree inside the furnace was 5×10. -3 Pa, heat to 680℃ and hold for 28 min to homogenize the temperature, then heat to 1130℃ at a rate of 11℃ / min and hold for 2.2 h. After holding, argon gas is introduced for quenching at a cooling rate of 50℃ / min to obtain the pipe base.

[0054] S2. By mass ratio, 19 parts calcium hydroxide, 29 parts boric acid, and 13 parts fumed silica were used as solid phase components. 43 parts deionized water and 0.9 parts sodium carboxymethyl cellulose were added. After pre-dispersion by mechanical stirring at 280 r / min for 50 min at room temperature, a modified suspension slurry was prepared by planetary ball milling. Zirconia grinding balls were used for ball milling, with a ball-to-material mass ratio of 5.5:1. The ball milling speed was 310 r / min, and the ball milling time was 2.2 h. The ball milling process was stopped for 5 min every 30 min for temperature control. The slurry after ball milling was filtered through a 300-mesh standard sieve, and the solid content of the obtained slurry was 58 wt%.

[0055] S3. Preheat the pipe substrate to 55℃, and apply modified suspension slurry to the inner wall of the pipe using a rotary coating method. After sealing both ends of the pipe, rotate it horizontally at a speed of 65 r / min for 18 min. During the rotation, the pipe simultaneously swings back and forth 14° along the axial direction. After standing for 8 min to allow the slurry on the inner wall to level, apply slurry to the outer wall of the pipe using an air spraying method. The spraying air pressure is 0.22 MPa, the spraying distance is 18 cm, the gun speed is 11 cm / s, and two coats are applied with a 7 min interval between coats. After coating, dry at 125℃ for 2.2 h. During the drying process, keep the pipe rotating at a low speed of 18 r / min to obtain a plain film layer on both the inner and outer walls with an overall thickness of approximately 35 μm.

[0056] S4. The pipe fittings coated with the base film are vertically suspended in the furnace and subjected to segmented heat treatment under an argon protective atmosphere: the temperature is increased to 410℃ at a rate of 6℃ / min and held for 1.2h; then increased to 910℃ at a rate of 3℃ / min and held for 4.5h; high-purity argon is introduced throughout the process, and the oxygen volume fraction in the furnace is 10×10⁻⁶. -6During the heat preservation stage, a slight positive pressure of 0.045 MPa was maintained; after the heat preservation was completed, argon convection cooling was used with a gas flow rate of 22 m³ / s. 3 / h, cooling rate 10℃ / min, cooling to room temperature.

[0057] S5. Under an argon protective atmosphere, the pipe fittings undergo a two-stage aging treatment: the temperature is increased to 760℃ at a rate of 6℃ / min and held for 13 hours; the temperature is then reduced to 660℃ in the furnace and held for 9 hours; after the holding period, the temperature is further reduced in the furnace to room temperature to obtain the finished pipe fittings.

[0058] Comparative Example 1 The difference between this comparative example and Example 2 is that calcium hydroxide is not added in step S2, while the remaining raw material ratios and preparation processes are the same as in Example 2.

[0059] Comparative Example 2 The difference between this comparative example and Example 2 is that boric acid is not added in step S2, while the remaining raw material ratios and preparation processes are the same as in Example 2.

[0060] Comparative Example 3 The difference between this comparative example and Example 2 is that no fumed silica is added in step S2, while the remaining raw material ratios and preparation processes remain the same as in Example 2.

[0061] Comparative Example 4 The difference between this comparative example and Example 2 is that ordinary micron-sized silica is used to replace fumed silica in step S2, while the remaining raw material ratios and preparation processes are the same as in Example 2.

[0062] Comparative Example 5 The difference between this comparative example and Example 2 is that the slurry coating and modification heat treatment processes in steps S2, S3, and S4 are omitted. The pipe is only prepared by vacuum solution treatment in step S1 and secondary aging treatment in step S5. The remaining process parameters are the same as those in Example 2.

[0063] To verify the service performance of the GH4099 high-temperature alloy corrosion-resistant pipe fittings prepared in this invention, the high-temperature composite hot corrosion performance and cold-heat cycle anti-stripping performance of the pipe fittings prepared in Examples 1 to 5 and Comparative Examples 1 to 5 were tested. Three parallel samples were set for each group, and the test results were taken as the average value of the parallel samples. Before testing, a wire EDM machine was used to cut sheet-like samples measuring 15mm × 10mm × 2mm from the same position on the straight pipe section of each set of pipe fittings. The original inner and outer surfaces of the pipe fittings were retained as the test surfaces. The sides produced by cutting were sealed with epoxy resin by cold mounting, exposing only the original test surfaces. After the resin cured, the edges of the non-test surfaces were polished with 400#, 800#, and 1200# wet sandpaper in sequence. Then, the samples were ultrasonically cleaned in acetone solution for 10 minutes, rinsed with anhydrous ethanol, dried with high-purity nitrogen, and placed in a desiccator to stand for 24 hours until constant weight. The initial mass of each sample was weighed using an electronic analytical balance with an accuracy of 0.01mg and recorded as m0 for later use.

[0064] (I) High-Temperature Composite Hot Corrosion Performance Test: The salt coating isothermal corrosion method was used to simulate the corrosion conditions of high-temperature flue gas containing sulfur and chlorine. Before the test, the corrosion medium was prepared by accurately weighing 7.5g of analytical grade anhydrous sodium sulfate and 2.5g of analytical grade sodium chloride, stirring and dissolving them in a beaker containing 800mL of deionized water. After the solute was completely dissolved, it was transferred to a 1000mL volumetric flask and diluted to volume to prepare a sodium sulfate-sodium chloride mixed corrosion solution with a total salt concentration of 10mg / mL. The solution was sealed and stored at room temperature for later use. During salt coating, the pretreated sample was completely immersed in the mixed corrosion solution. After immersion for 30s, it was removed vertically at a uniform speed and immediately placed in a preheated 120℃ drying oven for 10min. The immersion and drying operations were repeated. The sample mass was weighed after each drying until the salt film deposition on the sample surface was controlled at 2.5±0.5mg / cm³. 2 Record the mass m1 of the sample after salt coating.

[0065] The salt-coated samples were placed flat in a covered corundum crucible, with samples from the same group placed in the same crucible and not in contact with each other. The crucible was placed in a box-type high-temperature resistance furnace with a temperature control accuracy of ±1℃, and the temperature was increased to 900℃ at a rate of 5℃ / min, followed by timing and constant temperature holding. Heating was stopped at three time points: 20h, 50h, and 100h. The corresponding crucibles were removed and cooled to room temperature with the furnace. The samples were then removed and immersed in boiling deionized water for 5min. This process was repeated three times to thoroughly remove residual salts and loose corrosion products from the surface. The samples were then rinsed with anhydrous ethanol, dried with high-purity nitrogen, and placed in a desiccator to stand for 2h. The mass of the corroded samples at each time point was weighed using an electronic analytical balance and recorded as m. t After the test, the corrosion weight gain per unit area of ​​each group of samples was calculated using the formula Δm / S=(m t-m0) / S, where Δm / S is the corrosion weight gain per unit area, in mg / cm³. 2 The calculation result is the average of three parallel samples. The results are shown in Table 1: Table 1. Test results of high-temperature composite hot corrosion performance of each group of samples at 900℃ (II) Thermal Cycling Resistance Test: This test simulates temperature fluctuations during service to verify the bonding reliability between the modified layer and the substrate. During the test, the sample, after initial characterization, is placed in a box-type high-temperature resistance furnace preheated to 900℃. After holding at this temperature for 30 minutes, it is quickly removed and allowed to cool naturally in room temperature air for 5 minutes. This process is recorded as one thermal cycle. The furnace temperature is maintained at a constant 900℃ throughout the cycle. After every 20 thermal cycles, the sample is removed and placed under a stereomicroscope to observe the surface morphology of the modified layer. The number of cycles at which cracks, blistering, or localized peeling first appear is recorded. The cycle test is terminated after a cumulative total of 100 cycles. After the cyclic test, a peel test was performed using standard pressure-sensitive adhesive tape. The tape was flatly applied to the test surface of the sample, and pressed evenly with fingers to ensure complete adhesion between the tape and the sample surface. Then, the tape was peeled off quickly and uniformly in a direction perpendicular to the sample surface. This application and peeling operation was repeated three times, with a new tape used each time. The total mass difference of the tape before and after peeling was measured, and the amount of modified layer peeled off per unit area was calculated using the formula W=Δm. tape / S, where W is the amount of peeling per unit area, in mg / cm². 2 , Δm tape The mass difference before and after tape peeling is expressed in mg. The average value of three parallel samples from each group was used as the final result. The results are shown in Table 2. Table 2. Results of thermal cycling anti-stripping performance tests for each group of samples. As shown in Table 1, under the combined sulfur and chlorine-containing hot corrosion environment at 900℃, the corrosion weight gain per unit area in Examples 1-5 was at a low level after 20h, 50h, and 100h, with the corrosion weight gain after 100h being only 0.97-1.28 mg / cm³. 2The corrosion rate was significantly lower than that of the comparative samples, indicating that the GH4099 high-temperature alloy pipe fittings prepared by this invention possess excellent resistance to high-temperature composite hot corrosion. This invention constructs an in-situ gradient modification layer on the pipe fitting surface, forming a barrier structure where a calcium borosilicate complex salt phase and a dense oxide layer enriched in chromium and aluminum elements synergistically combine. The borosilicate glass phase fills the pores of the film, forming a continuous and dense physical barrier that effectively prevents the penetration of molten salts and corrosive ions into the substrate. Calcium stabilizes the surface oxide film structure, inhibiting the dissolution and damage of the original oxide film on the substrate by sulfate and chloride molten salts. Simultaneously, the transition layer formed by element diffusion ensures the continuity of the bond between the modified layer and the substrate, preventing corrosive media from penetrating along the interface, thereby significantly reducing the corrosion rate and improving long-term corrosion resistance. Comparative Examples 1-3 had the calcium hydroxide, boric acid, and fumed silica components removed, respectively. Comparative Example 4 replaced fumed silica with micron-sized silica. The corrosion weight gain of all four samples after 100 hours increased to 2.32-2.91 mg / cm³. 2 The corrosion resistance deteriorated significantly. This is because the absence of boric acid prevented the formation of a sufficient glassy phase during heat treatment to promote film sintering and densification, resulting in a significant increase in the porosity of the modified layer and easy penetration of corrosive media along the pores. The absence of calcium hydroxide prevented the formation of a stable calcium borosilicate complex salt phase, leading to decreased high-temperature chemical stability of the film and susceptibility to molten salt corrosion and dissolution. The absence of fumed silica or its replacement with micron-sized silica resulted in a loose film skeleton structure, insufficient reactivity, and decreased density and uniformity, all of which weakened the barrier and protective effect of the modified layer. Comparative Example 5, the unmodified substrate sample, showed the most severe corrosion, with a weight gain of 4.45 mg / cm² after 100 hours. This was due to the continuous dissolution-redeposition destruction of the original oxide film under the action of molten salt, rendering it unable to resist the erosion of the composite corrosive media. This further verified the significant improvement in corrosion resistance provided by the in-situ gradient modification layer.

[0066] As shown in Table 2, the modified layers in Examples 1-5 showed the first appearance of cracks or peeling after more than 60 cycles, and the peeling amount per unit area after 100 thermal cycles was less than 0.13 mg / cm². 2The modified layer of this invention exhibits excellent interfacial bonding stability and thermal shock resistance. Through elemental diffusion, it forms a metallurgically bonded diffusion transition layer with the substrate. The boron, silicon, and calcium elements are distributed in a continuous gradient decreasing along the depth direction, resulting in a smooth transition in the thermal expansion coefficient between the modified layer and the substrate. This effectively buffers the interfacial thermal stress generated during alternating hot and cold cycles, preventing film cracking and peeling caused by stress concentration. Simultaneously, the dense film structure and uniform component distribution reduce internal stress defects within the film, further enhancing structural stability under thermal cycling conditions. The modified layers of Comparative Examples 1-4 only experienced 21-42 initial peeling cycles, but the peeling amount increased significantly after 100 cycles, indicating significantly worse peeling resistance than the example group. This is because the lack of core components weakens the diffusion of elements during heat treatment, making it impossible to form a continuous and effective diffusion transition layer. The modified layer and the substrate are only mechanically bonded, and the interfacial bonding strength is greatly reduced. At the same time, the film density decreases and internal defects increase. During the hot and cold cycles, stress tends to concentrate at the defects, accelerating crack initiation and propagation, ultimately leading to premature cracking and peeling of the film.

[0067] In summary, this invention constructs an in-situ gradient modification layer on the surface of GH4099 high-temperature alloy pipe fittings. By leveraging the synergistic barrier effect of the surface calcium borosilicate complex salt phase and the dense oxide phase to inhibit the penetration of corrosive media, and by utilizing the metallurgical bonding structure with elemental gradient transition to alleviate interfacial thermal stress, the high-temperature composite hot corrosion resistance and the anti-stripping performance of the pipe fittings under thermal cycling can be significantly improved simultaneously.

[0068] In the description of this specification, the reference to terms such as "example," "various examples," etc., means that a specific feature, structure, material, or characteristic described in connection with that example or preparation is included in at least one example or preparation of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same example or preparation. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more examples or preparations.

[0069] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing a GH4099 high-temperature alloy corrosion-resistant pipe fitting, characterized in that, Includes the following steps: S1. After surface grinding, degreasing and cleaning, the GH4099 high-temperature alloy pipe blank is subjected to vacuum solution treatment to obtain the pipe substrate. S2. A modified suspension slurry was prepared by pre-dispersing and planetary ball milling using calcium hydroxide, boric acid, and fumed silica as solid phase components, deionized water as dispersion medium, sodium carboxymethyl cellulose, and calcium hydroxide as solid phase components. S3. The modified suspension slurry is coated on the inner wall of the pipe fitting using a rotary coating method, and the modified suspension slurry is coated on the outer wall of the pipe fitting using an air spraying method. After drying, a film layer is formed on the inner and outer surfaces of the pipe fitting. S4. Under an argon protective atmosphere, the pipe fittings coated with the base film are subjected to segmented heating heat treatment and then cooled to room temperature. S5. Perform a two-stage aging treatment on the pipe fittings under an argon protective atmosphere, and then cool them to room temperature in the furnace. In step S2, by mass ratio, calcium hydroxide: boric acid: fumed silica: deionized water: sodium carboxymethyl cellulose = (16-20): (26-30): (10-14): (40-44): (0.6-1.0).

2. The preparation method according to claim 1, characterized in that, In step S2, the planetary ball mill uses zirconia grinding balls with a ball-to-material mass ratio of (4-6):1, a ball milling speed of 280-320 r / min, a ball milling time of 1.5-2.5 h, and the solid content of the resulting slurry is 50-60 wt%.

3. The preparation method according to claim 1, characterized in that, In step S3, the process parameters for rotary coating are as follows: after sealing both ends of the pipe, rotate horizontally at a speed of 50-70 r / min and a rotation time of 10-20 min; the process parameters for air spraying are as follows: spraying air pressure of 0.15-0.25 MPa, spray distance of 10-20 cm, gun speed of 8-12 cm / s, 1-3 coats, and an interval of 3-8 min between coats.

4. The preparation method according to claim 1, characterized in that, In step S3, the drying temperature is 110-130℃, the drying time is 1.5-2.5h, and the thickness deviation between the inner and outer walls of the resulting raw film layer is ≤±2μm.

5. The preparation method according to claim 1, characterized in that, In step S4, the segmented heating heat treatment process is as follows: the temperature is increased to 380-420℃ at a rate of 4-6℃ / min and held for 0.5-1.5h; then the temperature is increased to 880-920℃ at a rate of 2-4℃ / min and held for 3-5h; high-purity argon gas is introduced throughout the heat treatment process, and the oxygen volume fraction in the furnace is ≤10×10⁻ 6 After the heat preservation is completed, argon gas is used for convection cooling at a rate of ≥10℃ / min.

6. The preparation method according to claim 1, characterized in that, In step S1, the surface polishing is carried out sequentially using 400#, 800#, and 1200# wet sandpaper until the surface roughness Ra ≤ 0.8 μm; the degreasing and cleaning is performed by ultrasonic cleaning with acetone followed by rinsing with anhydrous ethanol and drying with nitrogen; the vacuum solution treatment process is as follows: the vacuum degree in the furnace is ≤ 5 × 10⁻³ Pa, the temperature is raised to 1100-1140℃ at a rate of 8-12℃ / min, and held for 1.5-2.5h. After the holding period, argon gas is introduced for quenching, and the cooling rate is ≥ 50℃ / min.

7. The preparation method according to claim 1, characterized in that, In step S5, the secondary aging process is as follows: the temperature is increased to 730-770℃ at a rate of 4-6℃ / min, held for 10-14h, and then cooled with the furnace after the holding period.

8. A GH4099 high-temperature alloy corrosion-resistant pipe fitting prepared by the method described in claim 1, characterized in that, The device includes a GH4099 nickel-based high-temperature alloy pipe substrate, wherein an in-situ gradient modification layer is provided on the inner and outer surfaces of the pipe substrate; the in-situ gradient modification layer includes a surface modification layer and a diffusion transition layer from the surface to the inside, and the diffusion transition layer is metallurgically bonded to the pipe substrate.

9. The GH4099 high-temperature alloy corrosion-resistant pipe fitting according to claim 8, characterized in that, The thickness of the surface modification layer is 20-30 μm, and the thickness of the diffusion transition layer is 5-8 μm.

Citation Information

Patent Citations

  • Titanium-aluminum alloy surface thermal diffusion protective coating and preparation method thereof

    CN122303785A

  • Hot corrosion-resistant coatings and components protected therewith

    US20120244383A1